Simulation of a smart antenna system - Rosli, Nur Alina Zureen (2008)
Smart Antenna technologies will change the economics of 3G radio networks. They provide either a major data capacity gain or a significant reduction in the number of base stations required to achieve a base level of service. When deployed optimally, Smart Antennas can increase the capacity of a network by more than 100% or reduce the required number of base stations to less than 50%. It is not surprising that Smart Antennas are more expensive than conventional technologies. These costs are a fraction on the gain achieved, but they mean that smart deployment will produce the most cost-effective result. This thesis is an overview of Smart Antenna technology, their benefits, how they work and how they can be deployed to best advantage. Implementation that revolves around the Least Mean Square (LMS) adaptive algorithm, chosen for its computational simplicity and high stability algorithm into the MATLABÂ® simulation of an adaptive array of a smart antenna base station system, is to investigate its performance in the presence of multipath components and multiple users. The simulations illustrate that adaptive array antenna systems are able to adjust their antenna pattern to enhance desired signals, and reduce interference.